2003
DOI: 10.1007/s10067-003-0784-4
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive and atypical manifestations of Erdheim-Chester disease

Abstract: Erdheim-Chester disease (ECD) is a disseminated non-Langerhans' cell histiocytosis with multisystem involvement, including characteristic sclerotic musculoskeletal lesions. We present the case of a 27-year-old woman with a fulminant course and atypical involvement by ECD manifesting as extensive cerebrovascular disease and lytic musculoskeletal lesions. This case represents an unusual and aggressive presentation of ECD owing to the patient's young age, the severity of the cerebrovascular involvement and the ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 10 publications
1
8
0
3
Order By: Relevance
“…2,5,12 This finding is also in contradistinction to the focal mass lesions reported in the supratentorial compartment. 12,14,15,19,20 The final patient demonstrated diffuse FLAIR signal-intensity hyperintensity, similar to findings in a previous report by Bianco et al 21 HPA involvement has been reported as a single micronodular or nodular infundibular stalk mass 5 or thickening of the pituitary stalk. 12 This is similar to the findings in 3 patients in our study who demonstrated linear thickening of the pituitary stalk.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…2,5,12 This finding is also in contradistinction to the focal mass lesions reported in the supratentorial compartment. 12,14,15,19,20 The final patient demonstrated diffuse FLAIR signal-intensity hyperintensity, similar to findings in a previous report by Bianco et al 21 HPA involvement has been reported as a single micronodular or nodular infundibular stalk mass 5 or thickening of the pituitary stalk. 12 This is similar to the findings in 3 patients in our study who demonstrated linear thickening of the pituitary stalk.…”
Section: Discussionsupporting
confidence: 75%
“…The second novel manifestation of ECD was ependymal enhancement along the lateral ventricle with linear extension inferiorly into the lentiform nucleus. Previous reports have described the presence of focal intra-axial mass lesions of the white matter and basal ganglia 12,14,15 but not this ependymal or linear enhancement. Several targeted treatments, including interferon and imatinib, have recently shown efficacy in ECD.…”
Section: Discussionmentioning
confidence: 99%
“…The related radiographic findings are diffuse or patchy opacities of the tibia and/or fibula, medullary sclerosis and cortical thickening of the metaphyseal and diaphyseal portions without epiphyseal changes. On 99 mTc scintigraphy, intense, bilateral and symmetrical tracer uptake by the long-bone diaphyses and metaphyses is revealed, reflecting increased osteoblastic activity in those regions [15][16][17][18][19][20][21]. In our series, osteosclerotic changes were seen in the metaphyseal and diaphyseal portions of the tibia and fibula in three patients (1, 3 and 4).…”
Section: A B Cmentioning
confidence: 81%
“…La scintigrafia 99 mTc evidenzia intensa iperfissazione, bilaterale, simmetrica a carico delle diafisi e metafisi delle ossa lunghe, conseguente ad aumento dell'attività osteoblastica in tali sedi [15][16][17][18][19][20][21]. In tre pazienti (casi 1, 3 e 4) the osteosclerotic changes were seen at the femoral level.…”
Section: A B Cunclassified
“…Exophtalmos and xantoma-like lesions of eyelids are also common; other ophthalmological findings consist of ophthalmoplegia, optic disc swelling, up to blindness due to optical atrophy [7]. Central nervous system infiltration is rather infrequent, mainly presenting with pyramidal, cerebellar or brainstem symptoms, or deteriorating mental functioning [8][9][10]. Middle-aged men and women seem to be equally affected.…”
Section: Introductionmentioning
confidence: 99%